Suppressing Charge Disproportionation of MnO2 Cathodes in Rechargeable Zinc Ion Batteries via Cooperative Jahn‐Teller Distortion. Issue 12 (29th September 2021) - Heo, Jiyun; Chong, Sanggyu; Kim, Soohyun; Kim, Riyul; Shin, Kyungjae; Kim, Jihan; Kim, Hee‐Tak
Abstract: MnO2 is a promising candidate material as intercalative cathodes in rechargeable aqueous zinc ion batteries (ZIBs). It is renowned for its low cost, minimal toxicity, and high energy density; however, severe capacity fading from the dissolution of MnO2 remains a critical challenge that must be overcome to achieve improved cycling performance. In this study, surface coating of MnO2 with dicyandiamide is proposed as a method to significantly reduce the dissolution of MnO2 by addressing the fundamental cause of MnO2 dissolution, which is the charge disproportionation (CD) reaction of Mn 3+ . Experimental and computational methods are used to demonstrate that the surface coating triggers cooperative Jahn‐Teller distortion of Mn 4+ to alleviate lattice distortion and impede the CD reaction. Thus, the cycling stability of MnO2 is significantly improved, exhibiting 170 % higher capacity in comparison with pristine MnO2 and 99.9 % coulombic efficiency under a 1C rate condition. Resolving the orbital degeneracy with surface modification will open a new and prospective path for superior cycling performance of MnO2 ‐based ZIBs. Abstract : Protected MnO2 for AZIB : Cooperative Jahn‐Teller distortion (CJTD) for alternative pathway to mitigate charge disproportionation (CD) reaction of MnO2 is presented for aqueous Zn ion battery. The strong π donor‐acceptor interaction between MnO2 and dicyandiamide causes CJTD of Mn 4+ and allows Mn 3+ to fully participate in JTD. Consequently, highly uniform lattice with alleviated Mn dissolution is observed as CD reaction of Mn 3+ is suppressed.